2019
DOI: 10.1093/mnras/sty3503
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing star formation at the outskirts of Sextans A: Spectroscopic detection of early-O type stars.

Abstract: With both nebular-and stellar-derived abundances of 1/10 Z ⊙ and low foreground extinction, Sextans A is a prime candidate to replace the Small Magellanic Cloud as reservoir of metal-poor massive stars and reference to study the metal-poor Universe. We report the discovery of two early-O type stars in Sextans A, the earliest O-stars with metallicity <1/7 Z ⊙ known to date, and two additional O9 stars. Colour-excess estimates towards individual targets, enabled by spectral typing, manifest that internal reddeni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…There is so far only one O star detected in a Z = 1/30 Z galaxy (Leo P, Evans et al 2019). There are a few hot massive stars detected in Local Group galaxies with metallicities between that of the SMC and 1/10 Z (Bresolin et al 2007;Evans et al 2007;Garcia & Herrero 2013;Hosek et al 2014;Tramper et al 2014;Camacho et al 2016;Garcia 2018;Garcia et al 2019). An emblematic galaxy in the low-metallicity range is I Zw 18 (Z ∼ 1/30−1/50 Z , Izotov et al 1999) in which Izotov et al (1997) reported the detection of Wolf-Rayet stars (see also Brown et al 2002).…”
Section: Spectroscopic Sequences At Z = 1/30 Zmentioning
confidence: 99%
See 1 more Smart Citation
“…There is so far only one O star detected in a Z = 1/30 Z galaxy (Leo P, Evans et al 2019). There are a few hot massive stars detected in Local Group galaxies with metallicities between that of the SMC and 1/10 Z (Bresolin et al 2007;Evans et al 2007;Garcia & Herrero 2013;Hosek et al 2014;Tramper et al 2014;Camacho et al 2016;Garcia 2018;Garcia et al 2019). An emblematic galaxy in the low-metallicity range is I Zw 18 (Z ∼ 1/30−1/50 Z , Izotov et al 1999) in which Izotov et al (1997) reported the detection of Wolf-Rayet stars (see also Brown et al 2002).…”
Section: Spectroscopic Sequences At Z = 1/30 Zmentioning
confidence: 99%
“…the wavelength range 4500−8000 Å which will be probed by HARMONI and MOSAIC. We selected this range for the following reasons: it contains a fair number of lines from different elements; at these wavelengths, OB stars emit more flux than in the near-infrared; Local Group dwarf galaxies have relatively low extinction (Tramper et al 2014;Garcia et al 2019). We therefore anticipate that it will be more efficient to detect and characterize new OB stars in this wavelength range.…”
Section: Optical Wavelength Range Of the Eltmentioning
confidence: 99%
“…While the quantitative spectroscopy of individual, hot, massive stars is also possible nowadays in galaxies further away (e.g. Garcia et al 2019), such studies are only in their infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Extremely metal-poor H regions give their name to extremely metal-poor galaxies (XMPs), which are arbitrarily defined to have O/H ≤ (O/H) /10 in the ionized gas (Kunth & Östlin 2000), or equivalently, using 12+log(O/H) = 8.69 as the solar reference value (Asplund et al 2009), 12+log(O/H) ≤ 7.56. 1 Unfortunately, the three known nearby XMPs where individual massive stars can be observed (Sextans A, SagDIG, and Leo P) are not strongly starforming (Camacho et al 2016;Garcia 2018;Garcia et al 2019;Evans et al 2019). Thus, their stars do not significantly cover the parameter space of mass, luminosity, effective temperature, age, rotation, dynamical interaction in dense massive clusters, and in the case of stars in binary systems, orbital parameters and mass ratio combinations, which is relevant for either OB-type star astrophysics or as a reference to model distant starburst galaxies.…”
Section: Introductionmentioning
confidence: 99%